Accounting for Social Responsibility and Its Applicability in Islamic banks: An Analytical Study in Saudi Arabia - Al-Balawi, Reem Mohammed (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the understanding Islamic banks in Saudi Arabia of the concept of social responsibility accounting, identify the most important obstacles to the application of social responsibility accounting in Islamic banks in Saudi Arabia, and to know the extent to which Islamic banks in Saudi Arabia apply social responsibility accounting with its three areas of (community service, human resources, and customers). The study used the descriptive analytical approach, the sample of the current study consisted of (102) employees of Islamic banks in Saudi Arabia. The results of the study showed that Islamic banks in Saudi Arabia are aware about the concept of social responsibility accounting, and there are many obstacles to the application of social responsibility accounting in banks, and the results showed that the application of banks of the areas of social responsibility accounting (customers, human resources, community service) with a high degree. The study recommended the development of the trends of economic institutions towards the use of the social responsibility accounting system.